Integrated multi-omics reveals the relationship between growth performance, rumen microbes and metabolic status of Hu sheep with different residual feed intakes - Yanzhen Zhang; Xiaowei Zhang; Dingren Cao; Jinyong Yang; Huiling Mao; Lingling Sun; Chong Wang (Animal Nutrition)
Residual feed intake (RFI) is a metric that provides a more accurate measure of feed efficiency. The lower the RFI, the higher the feed efficiency. The changes in the host microbiome and metabolome contribute to the greater feed efficiency of low RFI (LRFI) animals. The aim of this study was to explore the differences in rumen microorganisms, rumen metabolites and plasma metabolites of Hu sheep with differing RFI through the microbiome and metabolome. A total of 80 Hu sheep were used. The experiment consisted of a 15-d pretrial period and a 128-d experimental period. The RFI in the experimental period was calculated for all sheep, and the sheep were screened into high RFI (HRFI, n = 8) and LRFI (n = 8) groups. The HRFI and LRFI sheep did not differ in their initial and final body weights, average daily gain and body measurements, but the dry matter intake of LRFI sheep was significantly decreased (28.4%, P < 0.001). The sheep with LRFI had higher digestibility of crude protein (P = 0.010) and ether extract (P = 0.010) compared to HRFI group. The concentrations of acetate (P = 0.036), propionate (P = 0.010), valerate (P = 0.027) and total volatile fatty acids (P = 0.048) in rumen of LRFI group were higher compared to HRFI group. The results of 16S rDNA sequencing indicated that the sheep with LRFI had higher proportions of Prevotella genus in rumen liquid (P = 0.031). The rumen metabolome and plasma metabolome results showed that the citrate cycle, pyruvate metabolism and alanine, aspartate and glutamate metabolism processes were more active for sheep in LRFI group, which provided more energy substrate such as malic acid, oxoglutaric acid and citric acid. In conclusion, sheep with LRFI can utilize feed more efficiently, and the more active energy metabolism pathway and the production of energy substances may account for the higher feed efficiency.